A novel natural-derived pentameric peptide protects from angiotensin-evoked high blood pressure. (14th October 2021) - Carrizzo, A; Basilicata, M G; Pepe, G; Ciccarelli, M; Di Pietro, P; Campiglia, P; Vecchione, C
Abstract: Background: Arterial hypertension is the most important risk factor for cardiovascular diseases, myocardial infarction, heart failure, renal failure and peripheral vascular disease. In the last decade, milk-derived bioactive peptides have attracted attention for their beneficial cardiovascular properties. Methods: Here we combined in-vitro chemical assay such as LC-MS/MS analysis of buffalo ice cream, ex-vivo vascular studies evaluating endothelial and smooth muscle responses using pressure myograph, and translational assay testing in-vivo the vascular actions of PG1 administration in murine models. Results: We demonstrate that a novel buffalo ice-cream-derived pentapeptide "QKEPM", namely PG1, is a stable peptide that can be obtained at higher concentration after gastro-intestinal digestions (GID) of buffalo ice-cream (BIC). It owns potent vascular effect in counteract the effects of angiotensin II-evoked vasoconstriction and high blood pressure levels. Its effects are mediated by the inhibitory effect on AT1 receptor leading to a downregulation of p-ERK½/Rac1-GTP and consequent inactivation of NADPH oxidase activity. Conclusions: These results strongly candidate PG1, as a novel bioactive peptide for the prevention and management of hypertension, thus expanding the armamentarium of preventive strategies aimed at reducing the incidence and progression of hypertension and its related cardiovascular complications. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): University